Tokophobia: A dread of pregnancy - Manjeet Singh Bhatia (Industrial Psychiatry Journal, 2012)
Tokophobia is a pathological fear of pregnancy and can lead to avoidance of childbirth. It can be classified as primary or secondary. Primary is morbid fear of childbirth in a woman, who has no previous experience of pregnancy. Secondary is morbid fear of childbirth developing after a traumatic obstetric event in a previous pregnancy. A case of tokophobia with depression who responded to fluoxetine is being described.